Aroma release and retronasal perception during and after consumption of flavored whey protein gels with different textures. Part I: in vivo release analysis. - Mestres, Montse; Moran, Noelia; Jordan, Alfons; Büttner, Andrea (Journal of Agricultural and Food Chemistry, 2005)
The influence of gel texture on retronasal aroma release during mastication was followed by means of real-time proton-transfer reaction mass spectrometry and compared to sensory perception of overall aroma intensity. A clear correlation was found between individual-specific consumption patterns and the respective physicochemical release patterns in vivo. A modified data analysis approach was used to monitor the aroma changes during the mastication process. It was found that the temporal resolution of the release profile played an important role in adequate description of the release processes. On the basis of this observation, a hypothesis is presented for the observed differences in intensity rating.<br